Perbedaan asupan zat gizi, pengetahuan anemia, dan kepatuhan konsumsi Tablet Tambah Darah (TTD) pada remaja putri di pesantren dan nonpesantren - Alfianti, Esya Aqilla; Dieny, Fillah Fithra; Kurniawati, Dewi Marfu’ah; Wijayanti, Hartanti Sandi (Jurnal Gizi Klinik Indonesia, 2024)
Differences in nutrient intake, anemia knowledge, and adherence to blood supplement tablet consumption between adolescent girls in Islamic boarding schools and non-Islamic boarding schoolsBackground: Anemia is a nutritional problem that often occurs in adolescent girls, especially in Islamic boarding schools, where the prevalence of anemia in adolescent girls reaches >40%. Factors causing anemia in adolescent girls include a lack of iron, protein, and folate intake, low knowledge of anemia, and a lack of consumption of blood supplement tablets.Objective: This study aimed to analyze the differences in nutrient intake, knowledge of anemia, and adherence to blood supplement tablet consumption between adolescent girls in boarding schools and non-boarding schools.Methods: This study was observational-analytic with a cross-sectional design. The subjects were 24 adolescent girls at PP Al-Uswah (an Islamic boarding school group) and 24 at SMAN 12 Semarang (a non-Islamic boarding school group). The study variables were nutrient intake, anemia knowledge, and adherence to blood supplement tablets. Statistical analysis used an independent sample t-test of normally distributed and a Mann-Whitney test if not normally distributed.Results: There were significant differences in the knowledge of anemia (p<0.001) and protein intake (p = 0.003) from both groups. The non-boarding school group had higher anemia knowledge and protein intake than the boarding school group. Iron intake, folate intake, and adherence to blood supplement tablet consumption in both groups showed no significant difference (p > 0.005).Conclusions: Adolescent girls in boarding and non-boarding schools significantly differed in protein intake and knowledge of anemia. There was no significant difference in adherence to blood supplement tablet consumption between them.